To determine whether the values \(-1\) and \(\frac{7}{3}\) are solutions to the equation \(3x^2 - 4x - 4 = 3\), we first simplify the equation. We can rewrite it as:
\[ 3x^2 - 4x - 4 - 3 = 0 \]
This simplifies to:
\[ 3x^2 - 4x - 7 = 0 \]
Now, we will substitute each candidate value into this simplified equation and check if it satisfies the equation.
Testing \(x = -1\):
Substituting \(x = -1\):
\[ 3(-1)^2 - 4(-1) - 7 = 3(1) + 4 - 7 = 3 + 4 - 7 = 0 \]
Since the left-hand side equals 0, \(x = -1\) is a solution.
Testing \(x = \frac{7}{3}\):
Substituting \(x = \frac{7}{3}\):
\[ 3\left(\frac{7}{3}\right)^2 - 4\left(\frac{7}{3}\right) - 7 \] Calculating \(\left(\frac{7}{3}\right)^2\):
\[ \left(\frac{7}{3}\right)^2 = \frac{49}{9} \]
Then,
\[ 3\left(\frac{49}{9}\right) - 4\left(\frac{7}{3}\right) - 7 = \frac{147}{9} - \frac{28}{3} - 7 \] Converting \(\frac{28}{3}\) and \(7\) to ninths:
\[ \frac{28}{3} = \frac{84}{9} \quad \text{and} \quad 7 = \frac{63}{9} \]
Now substituting back:
\[ \frac{147}{9} - \frac{84}{9} - \frac{63}{9} = \frac{147 - 84 - 63}{9} = \frac{0}{9} = 0 \]
Since the left-hand side equals 0, \(x = \frac{7}{3}\) is also a solution.
Conclusion:
Both \(x = -1\) and \(x = \frac{7}{3}\) are solutions.
Therefore, the response is:
Both \(x = -1\) and \(x = \frac{7}{3}\) are solutions.